Migraine Headache associated with Multiple Sclerosis: Results from the Nationwide Inpatient Sample - Koffman, Boyd (Translation: The University of Toledo Journal of Medical Sciences, 2021)
Background: Multiple Sclerosis (MS) is an immune-mediated disease that targets and injures myelin and axons in the central nervous system. A high prevalence of migraine headache has been reported among MS patients. In this study, we investigated variables affecting migraine headache occurrence in MS patients. Methods: The Health Cost and Utilization Project (HCUP) Nationwide Inpatient Sample (NIS) data was utilized. MS hospitalizations (“cases”) were identified by ICD-9-CM code 340. Non-MS Hospitalizations were matched to cases 1:1 by age and gender. Results: We identified 18955 MS patients between 2010 and 2013. The prevalence of migraine among MS patients (7%) was significantly higher than the control group (2.8%). Unspecified Migraine constituted the highest percentages of migraine subtype in both groups. All subtypes of headache, except migraine without aura, were significantly higher among MS patients compared to the control group. Among MS patients, younger age, white race, female gender, depression, and obesity were significant predictors of migraine. Conclusions: Our study provides prevalence data for different subtypes of headache and confirms depression and obesity as risk factors for migraine.